PENGARUH DIVERSITY TUGAS DAN LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA PEGAWAI DINAS PERTANIAN DAN PERKEBUNAN KABUPATEN BIREUN - Yanto, Ferri; Yanti, Ira Dama; Fauzan, Fauzan (Fakultas Ekonomi, 2025)
This study will aim to analyze influence of Task Diversity and Work Environment on Employee Work Motivation, taking the number of respondents as a research sample of 68 respondents who are Civil Servants who work at the Agriculture and Plantation Office of Bireuen District to distribute questionnaires. The analysis method used in this research is multiple linear regression analysis where this analysis can be used to see the relationship and influence between the variables studied.Based on the analysis and calculation of the research results, a very strong and positive relationship was obtained between Task Diversity and Work Environment on Employee Work Motivation, with a correlation coefficient of 0,861 and a linear equation Y = 10,859 + 0,320X1 + 0,270X2. The results showed a partial effect, where the Task Diversity variable (X1) had a tcount of 4,807 which was greater than the ttable value of 1,99714 with a significance of 0,000.and the Work Environment variable (X2) has a tcount of 2,681 which is greater than the ttable value of 1,99714 with a significance of 0,009 and there is a simultaneous influence between Task Diversity and Work Environment on Employee Work Motivation which is indicated by the Fcount value greater than the Ftable value (93,038 3,14) with a significance level of 0,000.The results of the study also show that the value of R2 = 74,1% means that the variation in Employee Work Motivation at the Agriculture and Plantation Office of Bireuen District can be explained by the Task Diversity and Work Environment variables. The remaining 25,9% is influenced by other variables not discussed in this study.